PENGARUH PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK YANG DIMEDIASI OLEH LOYALITAS PELANGGAN (Studi Pada Pelanggan Minimarket Indomaret Wilayah Sampang) - Ana Yulistia Kusuma; Chamariyah Chamariyah; Subijanto Subijanto (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2022)
This type of research is explanatory research, research approach using a quantitative approach, research data analysis using SEM program partial least squares (PLS). The population is 230 people, the research sample is 146 people, the sampling method uses the slovin formula. The aims of this research are 1). To find out and analyze the direct effect of promotion on product purchasing decisions at the Indomaret Minimarket in Sampang area; 2). To find out and analyze the direct effect of promotion on customer loyalty at Minimarket Indomaret Sampang area; 3). To find out and analyze the direct influence of service quality on purchasing decisions at the Indomaret Minimarket in the Sampang area; 4). To find out and analyze the direct influence of service quality on customer loyalty at Minimarket Indomaret Sampang area; 5). To find out and analyze the direct influence of customer loyalty on product purchasing decisions at the Indomaret Minimarket Sampang area; 6). To find out and analyze the direct effect of promotion on product purchasing decisions at Minimarket Indomaret Sampang area mediated by customer loyalty; 7). To find out and analyze the direct influence of service quality on product purchasing decisions at Minimarket Indomaret Sampang area mediated by customer loyalty. Based on data analysis using smart PLS, the results showed that: 1). Promotion on purchasing decisions has a positive and significant effect with Original Sample value of 0.296 and p-values of 0.000; 2). Promotion on customer loyalty has a positive and significant effect with the Original Sample value of 0.391 and p-values of 0.000; 3). Service quality on purchasing decisions has no significant positive effect with the Original Sample value of 0.077 and p-values of 0.244; 4). Service quality on customer loyalty has a significant positive effect with Original Sample value of 0.291 and p-values of 0.002; 5). Customer loyalty to purchasing decisions has a significant positive effect with the Original Sample value of 0.318 and p-values of 0.000; 6). Promotion on purchasing decisions mediated by consumer loyalty has a positive and insignificant effect with the Original Sample value of 0.124 and p-values of 0.004; 7). Service quality on purchasing decisions mediated by customer loyalty has no significant positive effect with Original Sample value of 0.093 and p-values of 0.005. The dominant influence is the effect of promotion on customer loyalty.